CLINICAL SAFETY OF IVERMECTIN TREATMENT IN NILE TILAPIA, Oreochromis niloticus - SILVA, H. C. P.; OLIVEIRA, S. L.; COSTA, C. C.; IBELLI, B. C. C.; CAVALLI, B. J.; SCARABEL, V. L.; ARACATI, M. F.; RODRIGUES, L. F.; BELO, M. A. A. (Ars Veterinaria, 2023)
Ivermectin belongs to the group of avermectins, a group of macrocyclic lactones produced by Streptomyces avermitilis, this drug is widely used in the treatment of endoparasitoses and ectoparasitosis in different species of mammals around the world. Based on this need to develop an adequate sanitary management of fish farms and the therapeutic importance of macrocyclic lactones, this study aimed to evaluate the clinical safety of ivermectin administered orally as part of the feed for Nile tilapia (O. niloticus). For this, 56 tilapias (O. niloticus), ±100g, were placed in 7 aquariums (n=8) with a capacity of 100 L of water, supplied with running water devoid of chlorine, with the following treatments being preserved: T0 (Control, untreated), T1 and T2 (treated with 125 and 625µg/kg-1 of ivermectin, respectively). Blood samples were collected for hemogram, leukogram and evaluation of serum biochemical parameters, in addition to organs such as spleen, liver and kidneys (cranial and caudal) for somatic evaluation. The results admired an increase in serum levels of ALT, AST and glycemia, a reduction in cholesterol and triglyceride values ​​at the highest dose, in addition to a decrease in total protein levels and liver somatic analysis. There was no change in hematological parameters, while the leukocyte profile indicated a significant increase in total leukocytes in treated tilapia with lymphocytosis and neutrophilia.. Therefore, treatment with high doses of ivermectin can harm the health of Nile tilapia, requiring additional studies to establish safe therapeutic protocols for these animals.